2008
DOI: 10.1063/1.2939560
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor-enriched single wall carbon nanotube networks applied to field effect transistors

Abstract: Substantial progress are reported on field effect transistors (FET) consisting of semiconducting single wall carbon nanotubes (s-SWNTs) without detectable traces of metallic nanotubes and impurities. This outstanding result was made possible in particular by ultracentrifugation (250,000g) of solutions composed of SWNT powders with polyfluorene as extracting agent in toluene. Such s-SWNTs processable solutions were applied to realize FET, embodying randomly or preferentially oriented nanotube networks prepared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
128
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 19 publications
6
128
0
Order By: Relevance
“…The Raman spectra provided proof of the separation of the met-and sem-SWNTs [50][51][52] . For the HiPco-produced SWNTs, based on the Kataura plot 53,54 , we can estimate the ratio of the sem-or met-SWNTs using the RBM region in the Raman spectra measured by excitation at 633 nm, which is a widely used method 31,36,43,55 . Compared with the spectrum of the as-produced SWNTs (black line in Fig.…”
Section: Synthesis Of Cp-mmentioning
confidence: 99%
See 2 more Smart Citations
“…The Raman spectra provided proof of the separation of the met-and sem-SWNTs [50][51][52] . For the HiPco-produced SWNTs, based on the Kataura plot 53,54 , we can estimate the ratio of the sem-or met-SWNTs using the RBM region in the Raman spectra measured by excitation at 633 nm, which is a widely used method 31,36,43,55 . Compared with the spectrum of the as-produced SWNTs (black line in Fig.…”
Section: Synthesis Of Cp-mmentioning
confidence: 99%
“…Moreover, we revealed that the PFO copolymers with a bulky optically active moiety could separate the right-and left-handed sem-SWNTs 35 . However, there are several serious problems when using PFOs; that is, difficulty in the removal of the wrapped PFOs from the SWNT/PFO composites 36,37 as well as their low extraction efficiency from the as-produced SWNTs 30,31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we experimentally demonstrate optical gain in carbon nanotubes at a wavelength of 1.3 µm at room temperature. Semiconducting SWNT (s-SWNT) extracted by the previously described polyfluorene (PFO) method [17] were drop cast on glass substrate. Pure s-SWNT thin films will be hereafter designated as sample A, while a control sample made with a blend of s-and m-SWNT will be named sample B.…”
mentioning
confidence: 99%
“…Composites of conducting polymers with carbon nanotubes (CNTs) [1][2][3] have attracted considerable attention in the past few years because of their potential applications in polymer light emitting diodes [4,5], photovoltaic cells and photodiodes [6], field effect transistors [7], optical limiting devices [8], supercapacitors [9], sensors [10], etc. In fact, the extensive and exhaustive applications of CNTs in the field of polymer composites has perhaps exhilarated the scientific community to consider nanotubes as a part of the polymer family [11] rather than as a novel nanotechnology product.…”
Section: Introductionmentioning
confidence: 99%